Common medical problems in children an indispensable guide for parents - Liew, Poo Cheng (Pelanduk, 1995)
The purpose of this book is to educate parents on the importance of early detection to prevent illnesses and other complications. With early detection, prompt diagnosis and proper treatment, many potentially serious illnesses and health conditions can be avoided, while the impact of others can be greatly lessened.